Recombineering strategies for developing next generation BAC transgenic tools for optogenetics and beyond - Ting, Jonathan T.; Feng, Guoping (Frontiers in Behavioral Neuroscience, 2014)
The development and application of diverse BAC transgenic rodent lines has enabled rapid progress for precise molecular targeting of genetically-defined cell types in the mammalian central nervous system. These transgenic tools have played a central role in the optogenetic revolution in neuroscience. Indeed, an overwhelming proportion of studies in this field have made use of BAC transgenic cre driver lines to achieve targeted expression of optogenetic probes in the brain. In addition, several BAC transgenic mouse lines have been established for direct cell-type specific expression of Channelrhodopsin-2 (ChR2). While the benefits of these new tools largely outweigh any accompanying challenges, many available BAC transgenic lines may suffer from confounds due in part to increased gene dosage of one or more ‘extra’ genes contained within the large BAC DNA sequences. Here we discuss this under-appreciated issue and propose strategies for developing the next generation of BAC transgenic lines that are devoid of extra genes. Furthermore, we provide evidence that these strategies are simple, reproducible, and do not disrupt the intended cell-type specific transgene expression patterns for several distinct BAC clones. These strategies may be widely implemented for improved BAC transgenesis across diverse disciplines.